Kajian Kedalaman Kemiskinan di Provinsi Papua dan Papua Barat Tahun 2021 - Dino, Marsandhi Evan; Budiasih, Budiasih (Politeknik Statistika STIS, 2023)
Poverty is one of the macroeconomic problems faced by all countries in the world, including Indonesia. One of the Indonesian government's programs to alleviate poverty is the Transfer to Regions and Village Funds (TKDD), namely the Non-Physical Special Allocation Fund (DAK). During the 2015-2021 period, the Non-Physical DAK allocated to the Provinces of Papua and West Papua increased and was the highest compared to other Provinces in Indonesia. However, the depth of poverty in these two provinces is also the highest in Indonesia. It is the researchers' suspicion that there is inefficiency in the Non-Physical DAK in the two provinces. The research objective is to identify the existence of technical efficiency problems and the influence of Non-Physical DAK on alleviating the depth of poverty in Papua and West Papua Provinces using Stochastic Fronter Analysis. The results of the study concluded that the government's efforts to reduce the depth of poverty in the provinces of Papua and West Papua were not as optimal as expected. There is a problem of non-physical DAK technical inefficiency in the two Provinces with more than 50% of Regencies/Cities in the two Provinces having a low level of efficiency in allocating funds in reducing the depth of poverty. The funds that were able to significantly reduce the depth of poverty in the two provinces were the Health Operational Assistance Fund and the Assistance for Early Childhood Education. The hope from this research is that the government will immediately evaluate and improve as soon as possible regarding the distribution of the non-physical DAK which is budgeted for so that these funds are more efficient in reducing the depth of poverty in the provinces of Papua and West Papua.